Regional Clustering Model of Covid-19 Cases at the Early of the Pandemic in Indonesia - Wibowo, Arief; Handoko, Andy Rio; Zarlis, Muhammad (International Journal of Intelligent Systems and Applications in Engineering, 2023)
President of the Republic of Indonesia Ir. Joko Widodo announced the first case of the COVID-19 virus in Indonesia on March 2, 2020. 2019-nCoV, the original name of this coronavirus, is becoming increasingly well known because it has become a pandemic in more than 60 countries in just two months since it was discovered. Only one month since this virus was found in Indonesia, almost 1,800 people have tested positive for Covid-19. DKI Jakarta Province is the epicenter of this virus pandemic, with the number of positive sufferers of more than 5600 people as of May 14, 2020. With this vast spread, DKI Jakarta was designated as the first province to implement Large-Scale Social Restrictions (PSBB) based on the Decree of the Minister of Health of the Republic of Indonesia as of April 7, 2020. This research aims to model the clustering of sub-district areas with positive COVID-19 cases in DKI Jakarta. The model was built using the K-Means algorithm, a clustering data mining algorithm that efficiently forms clusters from the past data learning process. The research data comes from the official Corona unique website in Jakarta, namely http://corona.jakarta.go.id, which was cross-tested with other sources, accompanied by elaboration with regional demographic data from the DKI Jakarta Provincial Government website. The research results show that clustering or grouping of areas in DKI Jakarta with the number of positive sufferers is formed at the value k=2 with a Davies Bouldin Index evaluation value of 0.182. The clustering pattern visualized as an electronic-based map can be connected to data on the favorable distribution of COVID-19 in sub-district areas in DKI Jakarta. Jakarta is the epicenter of the pandemic in Indonesia, so this research is important to find out how the country's capital region is clustered to face other pandemics in the future. The research results can be used by stakeholders in making decisions related to handling the COVID-19 pandemic, especially in the DKI Jakarta area, based on the regional clusters formed.